Qualidade fisiológica de sementes de Araucaria angustifolia (Bertol.) kuntze submetidas a diferentes condições de armazenamento e a escarificação - Álvaro Valente Caçola; Cassandro Vidal Talamini do Amarante; Frederico Dimas Fleig; Clenilso Sehnen Mota (Ciência Florestal, 2006)
The seeds of Araucaria angustifolia (Bertol.) Kuntze are recalcitrants and, therefore, they lose rapidly the viability after the harvest, limiting their use for nursery production of seedlings. This work was carried out to investigate the effects of cold storage duration, conservation method, and escarification on germination and vigour of seeds of Araucaria angustifolia. The seeds were cold stored (0-1oC/90-95% RH) for 0, 60, 120, and 180 days, under normal air condictions (NA), modified atmosphere (MA), and controlled atmosphere (CA) storage. For each cold storage duration, after removal from cold storage, the seeds were submitted or not to scarification (by cutting a small portion of the apical seed tegument, avoiding the damage of the endosperm), letting the germinate in a chamber with controlled environment, in plastic trays filled with vermiculite, for 60 days. The experiment followed the completely randomized factorial design (4x3x2), with four cold storage durations (0, 60, 120, and 180 days), three storage methods (NA, MA, and CA), with or without escarification, and four replicates. There was a good preservation of physiological quality for seeds submitted to different conservation methods in cold storage along the 180-day period. However, there was a faster germination and initial growth of seedlings for seeds left in cold storage for 60 days than in seeds assessed at harvest or left in cold storage for 120-180 days. The NA storage of seeds in perfurated plastic bags was as efficient as MA and CA storage to preserve seeds quality. Seeds scarification increased vigor and promoted seedlings initial growth of Araucaria angustifolia after being removed from cold storage.